Implementation of Cisco Packet Tracer–Based Learning Media Integrated with a Learning Management System (LMS) at SMK Bangun Negeri Hu’u - Imansyah, M. Nur; Supriyadin, Supriyadin; Prayudi, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of technology-based learning media is a strategic necessity in vocational education to improve instructional quality and teacher competence. Computer networking instruction often encounters limitations related to the availability of practical equipment and the high cost of laboratory infrastructure. This study aims to develop and implement learning media based on the Cisco Packet Tracer simulator integrated with a Learning Management System (LMS) using the ADDIE development model. This research employed a Research and Development approach involving 20 teachers from SMK Bangun Negeri Hu’u as research participants. Data were collected through practicality questionnaires, effectiveness questionnaires, and observations. The results indicate that the developed learning media achieved an average practicality score of 3.52 and an effectiveness score of 3.47 on a four-point Likert scale, both categorized as very good. These findings demonstrate that Cisco Packet Tracer–based learning media integrated with an LMS are practical and effective in supporting computer networking instruction in vocational high schools.